2017
DOI: 10.2471/blt.16.175844
|View full text |Cite
|
Sign up to set email alerts
|

Community-based approaches for neonatal survival: meta-analyses of randomized trial data

Abstract: ObjectiveTo analyse the impact of community approaches to improving newborn health and survival in low-resource countries.MethodsWe updated previous meta-analyses of published cluster randomized trials of community-based interventions for neonatal survival. For each study we extracted baseline data on the context: geographical area; available facilities and staffing; immediate breastfeeding and facility births; and neonatal mortality. We also extracted data on the primary outcome (neonatal survival) and interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…In the three months prior to the intervention, there were 137 admissions to the Other studies have shown that low cost interventions and training can improve neonatal practices and outcomes across Uganda and low and high middle income countries although many of these interventions have occurred in the community 10 setting. In a meta-analysis of 17 papers examining the effects of introducing pre and post-natal home visits and facilitated group meetings by trained community workers, did show an overall reduction in neonatal mortality (relative risk 0.86, 95% CI 0.82-0.89, p<0.001) [9]. A study of hospital admissions to a Ugandan hospital delivering neonatal care, highlighted that sepsis was the most common cause of admission (30%) [12].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the three months prior to the intervention, there were 137 admissions to the Other studies have shown that low cost interventions and training can improve neonatal practices and outcomes across Uganda and low and high middle income countries although many of these interventions have occurred in the community 10 setting. In a meta-analysis of 17 papers examining the effects of introducing pre and post-natal home visits and facilitated group meetings by trained community workers, did show an overall reduction in neonatal mortality (relative risk 0.86, 95% CI 0.82-0.89, p<0.001) [9]. A study of hospital admissions to a Ugandan hospital delivering neonatal care, highlighted that sepsis was the most common cause of admission (30%) [12].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the financial cost to the family unit of an infant death has been estimated at between US$6000 to US$11,000 in sub-Saharan Africa [6] and the overall cost of an infant death is estimated at 6% of gross domestic product (GDP) of all African countries [7]. women's meetings, had limited success with no significant change in mortality (RR 0.95, 95% CI 0.88 to 1.02) [9]. The trials included in the meta-analysis [9] reported difficulties implementing their interventions due to poor training and adherence of local clinical workers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While considering the context of Israel's current health system, the authors present existing innovative public health approaches that are informed by the community (Hanson et al. ) and advocated by the World Health Organization (Bishai et al. ).…”
Section: Sources Of Evidencementioning
confidence: 99%
“…In its exploration of different perspectives, it seeks to identify assumptions, gaps and meanings that delineate a position and direction for further inquiry (Kennett 2017). While considering the context of Israel's current health system, the authors present existing innovative public health approaches that are informed by the community (Hanson et al 2017) and advocated by the World Health Organization (Bishai et al 2015). The strategy is first to discuss the case of Israel and the advantages and disadvantages of the possible options, and second to present a new model that reorganizes existing structures, adds elements that invite community participation and infuses the system with an inclusive public health orientation.…”
Section: Sources Of Evidencementioning
confidence: 99%